Innovative School Principals and Restructuring - Dimmock, C.A.J (Taylor & Francis, 1996)
Restructuring is an international phenomenon, and great stress is placed on the role of the innovative principal in the process. This book offers insights into the ways in which six principals go about leading the change process in their schools, and looks for ways of understanding why and how principals behave and think in the way they do. Its edited topical life history approach identifies key events, experiences and significant others in the lives of the case study managers, and shows how these have shaped the way they implement changes to curriculum, teaching and learning in their schools.